Physical and chemical modifications in a humic cambissol under native grass after liming (Revista de Ciências Agroveterinárias, 2006)
Farmers are introducing annual crops under native grass utilizing different soil management and limestone application methods. In order to know better the changes of physical and chemical soil properties caused by these interferences , the effect of methods and rates of liming under native grass to corn cultivation were evaluated in the following systems: 1) NT 1.0i – no-tillage, incorporated liming at the experiment implantation , with rates of 0, 0.25, 0.5, 1.0 and 1.5 SMP; 2) NT 1.0s – no-tillage with superficial liming at the experiment implantation with the same rates; 3) NT 0.3s – no-tillage with superficial liming at the experiment implantation with the same rates divided and reapplied each three years. The completely randomized blocks design was used. The trial was set in a humic cambissol with native grass, located in Lages, SC. The soil had a water ph of 4.4. Its limestone necessity was 24 Mg ha-1 to rise to pH until 6.0. The following soil properties were determined: soil bulk density; soil particle density; macroporosity; microporosity; total porosity; penetration resistance; saturated hydraulic conductivity; aggregated stability; organic carbon; water ph; particle size distribution and flocculation degree by four layers of 0.05 m each, until the depth of 0.20 m. The incorporated limestone corrected soil acidity in the layer of 0-0.10 m, while the superficial limestone with integral rate corrected the layer of 0.0-0.05 m. Soil revolving with plowing and disk harrowing to incorporate limestone was beneficial to soil quality, reducing bulk density, microporosity, penetration resistance and increasing total porosity, macroporosity and flocculation degree. However, this soil preparation system also promoted loss of soil quality because it decreased the aggregate stability and the organic carbon content. The limestone rates, increased soil pH but did not modify soil physical properties.
Keywords: acidity correction methods; no-tillage; soil structure.